Representation of middle eastern countries in Geni Jora's novel: An analysis of travel literature according to Carl Thompson theory - Ilma, Awla Akbar; Manshur , Fadlil Munawwar; Sudibyo, Sudibyo (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2023)
This study aims to explain the representation of society and culture in Middle Eastern countries, including Morocco, Syria, and Jordan in the novel Geni Jora. The theory used is the theory of travel literature with the concept of representation of others according to Carl Thompson. Travel literature is a report about the world that is written based on the author's subjectivity and has a role in shaping the reader's knowledge. The results of the analysis show that the novel Geni Jora uses exploratory journey narratives and presents critical and courageous subjects. Morocco is described as a tolerant Islamic country because it succeeded in combining European modernity with past Islamic religiosity and Jewish culture. While Syria is described as a modern country, it is less religious and too Westernized. Likewise, Jordan is described as an Islamic country, but too westernized and inconsistent with Islamic ethics. The novel represents a contemporary travel literary genre that presents alternative and realistic narratives about the condition of the Middle East as a complex and diverse region. The novel also represents the contemporary travel genre which has not succeeded in narrating cosmopolitanism by still presenting competitive narratives and travel subjects that are superior when interacting with the characters encountered.